Modulation of Cell Death and Promotion of Chondrogenic Differentiation by Fas/FasL in Human Dental Pulp Stem Cells (hDPSCs) - Pisciotta, Alessandra; Bertani, Giulia; Bertoni, Laura; Di Tinco, Rosanna; De Biasi, Sara; Vallarola, Antonio; Pignatti, Elisa; Tupler, Rossella; Salvarani, Carlo; de Pol, Anto; Carnevale, Gianluca (Frontiers in Cell and Developmental Biology, 2020)
Human dental pulp stem cells (hDPSCs) are characterized by high proliferation rate, the multi-differentiation ability and, notably, low immunogenicity and immunomodulatory properties exerted through different mechanisms including Fas/FasL pathway. Despite their multipotency, hDPSCs require particular conditions to achieve chondrogenic differentiation. This might be due to the perivascular localization and the expression of angiogenic marker under standard culture conditions. FasL stimulation was able to promote the early induction of chondrogenic commitment and to lead the differentiation at later times. Interestingly, the expression of angiogenic marker was reduced by FasL stimulation without activating the extrinsic apoptotic pathway in standard culture conditions. In conclusion, these findings highlight the peculiar embryological origin of hDPSCs and provide further insights on their biological properties. Therefore, Fas/FasL pathway not only is involved in determining the immunomodulatory properties, but also is implicated in supporting the chondrogenic commitment of hDPSCs.